License to Pollute? Examining Environmental Permitting under Regional Autonomy in Indonesia - Yusuf, Wahyullah Ahmed; Humam, Achmad (Indonesian Journal of Environmental Law and Sustainable Development, 2024)
This paper delves into the intricacies of environmental permitting practices within the context of regional autonomy in Indonesia, scrutinizing whether the granting of permits inadvertently facilitates environmental degradation. It investigates the regulatory frameworks and enforcement mechanisms governing environmental permitting at the local level, shedding light on the potential trade-offs between economic development and environmental protection. Through empirical analysis and case studies, the paper uncovers the realities of environmental permitting under regional autonomy, revealing instances where lax regulations or inadequate enforcement have led to environmentally harmful activities. It examines the challenges faced by local authorities in balancing the need for economic growth with the imperative of environmental sustainability, highlighting the complex dynamics at play. Furthermore, the paper evaluates the effectiveness of existing environmental permitting mechanisms in mitigating pollution and safeguarding natural resources. It identifies gaps in regulatory oversight, shortcomings in monitoring and enforcement, and instances of regulatory capture or corruption that undermine the integrity of the permitting process. In conclusion, the paper underscores the importance of reevaluating environmental permitting practices under regional autonomy to ensure that permits are not inadvertently granting a "license to pollute." It calls for enhanced transparency, accountability, and community participation in the permitting process, alongside strengthened enforcement mechanisms and capacity-building initiatives to uphold environmental standards and promote sustainable development in Indonesia's decentralized governance landscape.